Common mental disorders and mental health-related quality of life among oral health providers - Carolina Franco de Azevedo; Juliane Kely Fagundes Silva; Higina Kelly Lemos Nogueira; Juliet Rocío Valdelamar Jiménez; Carolina Villa Nova Aguiar; Marta Silva Menezes; Liliane Lins Kusterer (Revista Cubana de Estomatología, 2022)
Introduction: Few studies are available about common mental disorders and mental health-related quality of life among dental healthcare providers.